Effect of brand equity on purchasing decisions (studies on tiktok shop consumers) - Ita Rahmawati; Fillafittrotun Nisa; Lailatus Sa’adah (Institute of Computer Science (IOCS), 2023)
Marketing is the activity of introducing products to consumers that aims to meet consumer needs. Competition in marketing is very tight, especially because technological developments provide a variety of e-commerce for marketing activities so that competitors will have their own way of marketing their products to customers. One marketing strategy that effectively influences purchasing decisions is brand equity. In this study, researches rs wanted to know the effect of brand equity on purchasing decisions at the Tiktok shop. tiktok shop is one of the e-commerce that is often used. The purpose of this study was to determine the effect of brand equity consisting of four variables, namely brand awareness, brand association, quality perspective, and brand loyalty on purchasing decisions. This research was conducted using by conducting a survey through distributing questionnaires to 100 respondents.Tiktok shop consumer respondents who had been determined on the sample. In this study, analytical techniques were used which included descriptive analysis, classical assumption test, multiple linear regression analysis, hypothesis testing, and the calculation of the coefficient of determination. The results of this study conclude that brand equity simultaneously influences purchase decisions. and partially, brand awareness has no influence on purchasing decisions. for brand associations, perceived quality, and brand loyalty have a significant influence on purchasing decisions.